Control of Hypertension In Pregnancy Study randomised controlled trial—are the results dependent on the choice of labetalol or methyldopa?. (11th August 2015) - Magee, LA; ,; von Dadelszen, P; Singer, J; Lee, T; Rey, E; Ross, S; Asztalos, E; Murphy, KE; Menzies, J; Sanchez, J; Gafni, A; et al.
Abstract : Objective: To determine whether the difference in outcomes between 'less tight' (target diastolic blood pressure [dBP] of 100 mmHg) versus 'tight' control (target dBP of 85 mmHg) in the CHIPS Trial (ISRCTN 71416914, http://pre-empt.cfri.ca/ ;CHIPS) depended on the choice of labetalol or methyldopa, the two most commonly used antihypertensive agents in CHIPS. Design: Secondary analysis of CHIPS Trial data. Setting: International multicentre randomised controlled trial (94 sites, 15 countries). Population or sample: A total of 987 women with non‐severe non‐proteinuric pregnancy hypertension. Methods: Logistic regression was used for comparisons of 'less tight' versus 'tight' control among women treated with labetalol (but not methydopa) versus methyldopa (but not labetalol). Analyses were adjusted for the influence of baseline factors, including use of any antihypertensive therapy at randomisation. Main outcome measures: Main CHIPS Trial outcomes: primary (perinatal loss or high‐level neonatal care for > 48 hours), secondary (serious maternal complications), birthweight < 10th centile, severe maternal hypertension, pre‐eclampsia, and delivery at < 34 or < 37 weeks. Results: Of 987 women in CHIPS, antihypertensive therapy was taken by 566 women at randomisation (labetalol 111 ['less tight'] versus 127 ['tight'] or methyldopa 126 ['less tight'] versus 117 ['tight']) and 815 women after randomisation (labetalol 186 ['less tight'] versus 247 ['tight'] and methyldopa by 98 ['less tight'] versus 126 ['tight']). Following adjustment, odds ratios for outcomes in 'less tight' versus 'tight' control were similar between antihypertensive groups according to 'at randomisation' and 'after randomisation' therapy. Conclusion: Outcomes for 'less tight' versus 'tight' control were not dependent on use of methyldopa or labetalol. Tweetable abstract: In the CHIPS Trial, maternal and infant outcomes were not dependent on use of labetalol or methyldopa. Tweetable abstract: In the CHIPS Trial, maternal and infant outcomes were not dependent on use of labetalol or methyldopa.